Pengaruh Advertising Dalam Komunikasi Pemasaran Terhadap Keputusan Pembelian Minuman Mixue di Sukabakti Tangerang - Herdiana, Vany; Delima, Isniyunisyafna Diah; Irianti, Een (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research is entitled "The Influence of Advertising in Marketing Communications on the Decision to Purchase Mixue Drinks in Sukabakti District, Tangerang". The aim of this research is to find out how much influence advertising in marketing communications has on the decision to purchase mixed drinks in the Sukabakti sub-district, Tangerang. This research uses advertising theory according to Jefkins (1995:16), where this theory explains how advertising is used in marketing communications. The paradigm used in this research is the positivism paradigm with quantitative research methods. Researchers used data collection techniques using questionnaires and data analysis techniques using a Likert scale. The population used in this research are people in Sukabakti Tangerang who have purchased Mixue with an average age of 21 – 30 years with a sample size of 100 respondents. This research uses the SEM-PLS (Partial Least Square) method using SmartPLS software version 4.0. The results of this research indicate that there is a positive influence of advertising in marketing communications on purchasing decisions.